Two ATP Binding Cassette G Transporters, Rice ATP Binding Cassette G26 and ATP Binding Cassette G15, Collaboratively Regulate Rice Male Reproduction . Issue 3 (21st September 2015) - Zhao, Guochao; Shi, Jianxin; Liang, Wanqi; Xue, Feiyang; Luo, Qian; Zhu, Lu; Qu, Guorun; Chen, Mingjiao; Schreiber, Lukas; Zhang, Dabing
Abstract : Two ATP binding cassette G transporters play a collaborative role in transferring lipidic molecules from tapetal cells for the development of anther cuticle and pollen exine. Abstract: Male reproduction in higher plants requires the support of various metabolites, including lipid molecules produced in the innermost anther wall layer (the tapetum), but how the molecules are allocated among different anther tissues remains largely unknown. Previously, rice ( Oryza sativa ) ATP binding cassette G15 (ABCG15) and its Arabidopsis ( Arabidopsis thaliana ) ortholog were shown to be required for pollen exine formation. Here, we report the significant role of OsABCG26 in regulating the development of anther cuticle and pollen exine together with OsABCG15 in rice. Cytological and chemical analyses indicate that osabcg26 shows reduced transport of lipidic molecules from tapetal cells for anther cuticle development. Supportively, the localization of OsABCG26 is on the plasma membrane of the anther wall layers. By contrast, OsABCG15 is polarly localized in tapetal plasma membrane facing anther locules. osabcg26 osabcg15 double mutant displays an almost complete absence of anther cuticle and pollen exine, similar to that of osabcg15 single mutant. Taken together, we propose that OsABCG26 and OsABCG15 collaboratively regulate rice male reproduction: OsABCG26 is mainly responsible for the transport of lipidic molecules from tapetal cells to anther wall layers, whereas OsABCG15 mainly is responsible for the export of lipidic molecules from the tapetal cells to anther locules for pollen exine development.